THE IMPACT OF SKIMMING & SCANNING TECHNIQUES ON STUDENTS READING COMPREHENSION OF DESCRIPTIVE TEXT - Afriani, Imro’atul Husna; Rohmah, St. Shabibatul; Wijaya, Nandi Risma (Nusantara Hasana Journal, 2022)
The objective of this research was to find out the impact of using skimming and scanning strategies towards the students’ reading comprehension at grade 2 (two) of Vocational High School Negeri 1 Banyuwangi . Reading comprehension refers to the readers’ ability to understand the information of reading text. The use of skimming and scanning strategies in teaching reading is expected to be able to improve the students’ reading comprehension. Data collection technique focus on participant observation, interviews, and documentation. Skimming and Scanning is the appropriate technique to find the main idea, key word and content of the text without read the whole of the text. These findings suggest that there is impact of using skimming and scanning strategies towards the students’ reading comprehension at grade grade 2 (two) of Vocational High School Negeri 1 Banyuwangi. It is suggested that the teacher uses skimming and scanning strategies for teaching reading.